KADAR PENGHAMBAT PENGURAIAN FIBRIN OLEH TROMBIN YANG TERGIATKAN (THROMBIN ACTIVATABLE FIBRINOLYSIS INHIBITOR) DI PASIEN KEGEMUKAN DENGAN DAN TANPA DIABETES MELLITUS - Mansyur Arif; Ichwani Meinard; Winni Agustiani (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2010)
Obesity will cause the development of insulin resistance and endothelial dysfunction through fat metabolism hormones and cytokines products. The metabolic disorders is hallmarked by the decrease of insulin function and will cause disorders of coagulation andfibrinolysis. Thrombin-activatable fibrinolysis inhibitor (TAFI) is a newly found glycoprotein that has a role in the balance of coagulationand fibrinolytic process. The aim of this study was to analyze the TAFI level in obese subjects with and without diabetes mellitus. A crosssectional study was carried out by collecting data from TAFI level measurements at Prodia Clinical Laboratory Jakarta and Makassarduring January-March 2008. The data was analyzed using t test with SPSS version 12.0. From 80 samples that match with the criteria,was found in four (4) diabetes mellitus patients and 76 subjects without diabetes mellitus. The mean TAFI level in obese subjects withdiabetes mellitus was 7.67 ug/ml and in obese subjects without diabetes mellitus was 8.10 ug/ml. The result of t test showed p = 0.58.There was no significant difference between TAFI level in obese subjects with and without diabetes mellitus.